Epidemiology, microbiology and clinical impacts of non-tuberculous mycobacteria in adult patients with cystic fibrosis - Zoltán Örlős; Lilla Katalin Lőrinczi; Balázs Antus; Imre Barta; Zsuzsanna Miklós; Ildikó Horváth (Heliyon)
Background: Due to its increasing prevalence and suboptimal treatment, non-tuberculous mycobacterial (NTM) infection is an emerging problem in patients with cystic fibrosis (CF). Detailed description of regional NTM prevalence and distribution, and identification of predictors of NTM acquisition in CF are essential to optimise treatment and surveillance guidelines. Methods: A retrospective, multi-center analysis was conducted between the years 2020 and 2022 on data from 232 adult patients registered in the Hungarian CF Registry in 2022. In a case-control analysis of NTM-positive (n = 39) and NTM-negative (n = 73) CF patients, demographic, clinical, and microbiological data were analysed to identify potential predictors for NTM acquisition. The distribution of NTM species, their antibiotic susceptibility patterns were also evaluated. Results: The prevalence of NTM-positive sputum increased from 4.7 % to 12.9 % over study period. The most prevalent NTMs were M. avium complex (41.0 %), M. abscessus complex (MABSC) (38.5 %) and M. xenopi (15.4 %). MABSC strains were highly resistant to doxycycline, fluoroquinolones, and sulfonamides, while amikacin, macrolides, tigecycline and linezolid were often effective. Forced expiratory volume in 1 s (FEV1) was lower in the NTM-positive group at the index date and 1 and 2 years before NTM detection (p < 0.01), predicting NTM infection. Previous NTM-positive sputum culture enhanced the risk of NTM reacquisition in the airway (odds ratio: 7). Conclusion: The results demonstrate a high prevalence of NTM in the Hungarian adult CF population and a high rate of multidrug-resistant MABSC isolates in their sputum. The risk of acquiring airway NTM is higher in CF patients with significantly impaired lung function and previous respiratory mycobacteriosis.